2018
DOI: 10.1037/hum0000093
|View full text |Cite
|
Sign up to set email alerts
|

A hypnosis framing of therapeutic horticulture for mental health rehabilitation.

Abstract: This article shows how hypnosis can provide a useful framework for understanding therapeutic horticulture. Within this framework, data from in-depth interviews with 12 volunteers attending Cherry Tree Nursery—a sheltered work project for people with severe mental illness—provided conceptual groupings of reported experiences: rapport, induction, change in conscious state, relaxation, a safe place, therapeutic change via reframing and symbolic thinking, and confidence boosting. Natural environments and nature-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Therapeutic relationships have been reported to account for as much variance in therapy outcomes as the treatment modality itself [53]. The crucial role of relationships in treatment and support has previously been discussed relative to greenspace programmes [54,55], and is further evidenced in the current study. Some participants stated that improving relationships was the most important long-term outcome, over and above reducing substance use.…”
Section: Social Selfsupporting
confidence: 56%
See 1 more Smart Citation
“…Therapeutic relationships have been reported to account for as much variance in therapy outcomes as the treatment modality itself [53]. The crucial role of relationships in treatment and support has previously been discussed relative to greenspace programmes [54,55], and is further evidenced in the current study. Some participants stated that improving relationships was the most important long-term outcome, over and above reducing substance use.…”
Section: Social Selfsupporting
confidence: 56%
“…Additional mechanisms which were said to facilitate improved relationships were feelings of acceptance, belonging, and a reduction in perceived stigma. While feelings of acceptance and reduced stigma have previously been reported on greenspace programmes [55,62,66], this study suggests that these mechanisms are particularly important for people with PSU who often experience higher levels of stigma compared to those with other mental health challenges [67]. Stigma has been shown to be associated with maintaining PSU, increasing the likelihood of drug and alcohol related harm, and reducing the likelihood of accessing support services [53,[68][69][70].…”
Section: Social Selfmentioning
confidence: 59%
“…It is important to note that for quantitative studies, we included only significant results in this synthesis. Removing stigma (of mental illness) 1 1 [154] Increased use of green space 1 1 [57] Note. In this overview, only significant (for quantitative studies) reported effects are summarized; a number indicates the number of studies indicating an outcome with reported (significant) effects; differences in the number of references and effects can occur due to multiple similar outcomes being assessed in single publications.…”
Section: Effects Of Participation In Green Space Creation On Other Ou...mentioning
confidence: 99%
“…We also included community-related benefits, such as higher community cohesion (30). Additionally, 13 studies note an increased connection to place, either in the form of higher place attachment [95,107,139,148], special connections with place [85,91,115,154], or strengthening local identity [114]. Studies frequently report on educational benefits and skill development (41).…”
Section: Effects Of Participation In Green Space Creation On Other Ou...mentioning
confidence: 99%
“…Attention to the natural world can induce the deepened state of absorption (Fleischner, 2011;Stevens, 2018) incumbent for the engagement of attention and relaxation that underly successful hypnotherapy. Such a clinical approach might even help counteract some of the damage wrought by societal fragmentation (Anthony & Soule, 1989;Pavel & Anthony, 2015;Smith, 2013).…”
Section: The Nature Of Clinical Hypnosismentioning
confidence: 99%